2013
DOI: 10.1021/jp406923d
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics Study of the Reaction of OH Radicals with C5–C8Cycloalkanes at 240–340 K using the Relative Rate/Discharge Flow/Mass Spectrometry Technique

Abstract: Rate constants of reactions of hydroxyl radical with cyclopentane (k1), cyclohexane (k2), cycloheptane (k3), and cyclooctane (k4) have been acquired at 240-340 K and a total pressure of about 1 Torr using the technique of relative rate combined with discharge flow and mass spectrometry (RR/DF/MS). At 298 K, the rate constants are determined using two reference compounds, which are averaged to be k1 = (4.81 ± 0.88) × 10(-12), k2 = (6.41 ± 0.85) × 10(-12), k3 = (10.30 ± 1.44) × 10(-12), and k4 = (1.42 ± 0.27) × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Singh et al, 2013) and the absolute value (5.02) of Droege et al(Droege and Tully, 1987). And the obtained KOH values for cyclohexane are highly consistent (3% or better) with the absolute values (7.14×10 -12 , 7.19×10 -12 ) obtained by Droege and Tully and Sprengnether et al (Droege and Tully, Comparison of Experimental in this work with the reported in the literature…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Singh et al, 2013) and the absolute value (5.02) of Droege et al(Droege and Tully, 1987). And the obtained KOH values for cyclohexane are highly consistent (3% or better) with the absolute values (7.14×10 -12 , 7.19×10 -12 ) obtained by Droege and Tully and Sprengnether et al (Droege and Tully, Comparison of Experimental in this work with the reported in the literature…”
supporting
confidence: 90%
“…The error, σ av , was given by: σ av = (1/σ ref1 +1/σ ref2 +…) -0.5 . b: (Demore and Bayes, 1999); c: (Mellouki et al, 1994); d: (Talukdar et al, 1994); e: (Atkinson and Arey, 2003); f: (Cox et al, 1980); g: (Morin et al, 2015); h: (Wilson et al, 2006); i: (Tully et al, 1986); j: (Edney et al, 1986); k: (Perry et al, 1976); m: (Greiner, 1970a) ; n: (Donahue et al, 1998); o: (Harris and Kerr, 1988); p: (Calvert et al, 2015); q: (Droege and Tully, 1987); r: (Singh et al, 2013); s: (Badra and Farooq, 2015) u: (Sprengnether et al, 2009); t: (Anderson et al, 2004); v: (Greiner, 1970b), y: (Crawford et al, 2011) ; z: (Li et al, 2006); L: (Shaw et al, 2020); w: (Atkinson et al, 1982); A: (Ferrari et al, 1996); B: (Sivaramakrishnan and Michael, 2009); D: (Bejan et al, 2018); F: (Ballesteros et al, 2015). 22% lower than the experimental value obtained in this study.…”
Section: N-octane (Nonane)mentioning
confidence: 99%
“…The H-abstracting species that were taken into consideration are H, O, OH, O2, HO2, CH3, CH3O2, CH3O and C2H5 (referred to as X in Figures 1 and 2 [18,20,[34][35][36][37][38][39][40], most of them are limited to a narrow temperature range (< 500 K) [18,36,37,39,40] or even just to a single temperature [34,35,38]. In this work we used rate coefficients for the cyclopentane + OH reaction based on the work of Sivaramakrishnan and Michael, who investigated this reaction using shocktube experiments between 813 to 1341 K [20].…”
Section: H-abstractionmentioning
confidence: 99%
“…In addition, rapid collection of data may be facilitated under flow conditions by in-line analysis, and examples employing UV, 2 IR, 3 Raman, 4 Fluorescence 5 and NMR spectroscopy, 6 as well as mass spectrometry 7 and HPLC, 8 have been reported for kinetic study of reactions conducted under steady-state continuous flow conditions. A drawback of using steady-state flow conditions for kinetic studies is that, except where it is feasible to vary the position of an analytical probe along the reactor pathway, 9 a separate experiment is needed for each time point.…”
Section: Introductionmentioning
confidence: 99%